Measuring Public Satisfaction with Dottoro’ta Digital-Based Home Care Services in Makassar City: A Servqual Study Using SEM-PLS - Nurul Wahdaniyah; Ulung Pribadi; Herpita Wahyuni; Inrinofita Sari (FAKULTAS DAKWAH UIN SALATIGA, 2025)
The Homecare Dottoro'ta service is an innovative health service based on home visits implemented by the Makassar City Government to improve access and the quality of public health services. This study aims to examine the influence of service quality dimensions on the satisfaction level of the community using the Home Care Dottoro'ta services. This study uses a quantitative approach with a survey method by distributing questionnaires to 96 respondents who are active users of the service. Data analysis was conducted using SEM-PLS software to analyze and test the hypotheses. The research results show that reliability, assurance, and empathy have a positive and significant impact on community satisfaction, with T-statistics values of 4.259 (P-value 0.000), 2.494 (P-value 0.013), and 2.647 (P-value 0.008), respectively. Meanwhile, tangible and responsiveness do not show significant influence, with T-statistics values of 6.000 (P-value 0.549) and 2.771 (P-value 0.441). These findings affirm that accuracy, trust in the competence of the staff, and an empathetic approach are the main determinants in shaping the perception of service satisfaction. This study recommends increased professionalism and humanistic communication from medical staff and a thorough evaluation of service dimensions that have not yet significantly contributed to public satisfaction to support the sustainability and optimization of Dottoro'ta Home Care services in Makassar City.